Revolusi sehat : Mengungkap fakta tersembunyi / Hiroyuki Kobayashi ; penerjemah Ellnovianty Nine, Kanya Puspokusumo - KOBAYASHI, Hiroyuki; Ellnovianty Nine; Kanya Puspokusumo (Mizan Pustaka, 2014)
xiv, 171 hlm.; 19 cm